The Role of Organizational Climate in Increasing the Commitment of DPD KNPI Karawang Members - Nugroho, Husen Saepudin; Hakim, Arif Rahman; Maulidia, Ananda Saadatul (Jurnal Indonesia Sosial Sains, 2024)
This research aims to determine the effect of organizational climate on organizational commitment. The research method used is quantitative with a causality research design. The data collection technique uses saturated samples, where the entire population is sampled. The population in this study were 110 members of the Karawang Regency Regional Executive Board of the Indonesian Youth National Committee, consisting of 97 men and 13 women. Data were collected using the Organizational Commitment Questionnaire (OCQ) and the organizational climate scale constructed by the researcher. Hypothesis testing was conducted with simple regression analysis using SPSS version 25.0 for Windows 64-bit. The results showed a significance value of 0.025 (P < 0.05), which means that there is a negative effect of organizational climate on organizational commitment in members of the Karawang Regency Indonesian Youth National Committee. The coefficient of determination (R Square) value of 0.045 indicates that 4.5% of the variation in organizational commitment is explained by organizational climate. In comparison, the remaining 95.5% is influenced by other factors not included in this study.